(untitled) (Archaeologia Adriatica, 2022)
The article examines two-part bow fibulae (of the Osor type, variant A, or II according to D. Glogović), which formed a part of female attire in the region of Liburnia during the 9th and 8th centuries BC. Given their bow shapes and long, decorated pins these fibulae can be related to the two-part bow fibulae with conical helices also of the Osor type. Therefore, it can be presumed that the two-part bow fibulae discussed here originally formed part of headdress decorations or elaborate hairstyles as well. Special attention is given to the presence of such fibulae at the site of Škocjan, both at the necropolis and within the hoard of Mušja jama. As the site in question is fairly distant from the main Liburnian region, the attested examples both of single-looped bow fibulae with two knobs and of two-part bow fibulae are interpreted in relation to Škocjan as a “sacred place” of supra-regional importance.